Self‐Strangulation Through A Sphygmomanometer: An Uncommon Suicide1. Issue 2 (17th November 2016) - Lo Pinto, Sara; Tacchella, Tiziana; Fossati, Francesca; Bonsignore, Alessandro; Ventura, Francesco
Abstract: Suicide by asphyxia is quite a common event in forensic practice and may be implemented in different ways. The authors report a unique case of a 16‐year‐old youth who committed suicide by means of a standard mercury sphygmomanometer. This manner of suicide has never been described in the literature reviewed. A complete forensic investigation led to the conclusion that the cause of death was mechanical asphyxia, ascribed to self‐strangulation by means of an atypical item. The victim suffered from attention‐deficit/hyperactivity disorder (ADHD) syndrome and was assisted by support teachers. He had a solitary and depressive personality. The exceptional nature of this case suggests that sphygmomanometers may be regarded as possible means of self‐strangulation. The case also highlights the importance of managing patients with psychiatric or cognitive disorders; indeed, particular caution is required to keep them away from objects that, although apparently harmless, can become lethal.